The relationship between skeletal muscle mass to visceral fat area ratio and metabolic dysfunction-associated fatty liver disease subtypes in middle-aged and elderly population: a single-center retrospective study - Xing, Mengchen; Ni, Yanlan; Zhang, Ye; Zhao, Xiaoqian; Yu, Xin (Frontiers in Nutrition, 2023)
Background: It has been reported that decreased muscle mass combined with excessive visceral adipose tissue are significantly correlated with the risk of NAFLD. However, it has not been explored among populations with metabolic dysfunction-associated fatty liver disease (MAFLD) subtypes. We aimed to investigate whether appendicular skeletal muscle mass to visceral fat area ratio (SVR), an indicator of sarcopenic obesity, influences on the risk of MAFLD subtypes and its hepatic condition in middle-aged and elderly population. Methods: A total of 4003 middle-aged and elderly subjects were finally enrolled in this single-center retrospective study. Abdominal ultrasonography was employed for hepatic steatosis diagnosis. Participants were divided into four groups: diabetes-MAFLD、overweight/obese-MAFLD、lean-MAFLD and no MAFLD. Appendicular skeletal muscle mass as well as visceral fat area (VAF) was estimated by bioimpedance analysis measurements. Liver fibrosis was defined as a Fibrosis-4 index (FIB-4) and the NAFLD Fibrosis Score (NFS). Multivariate logistic regression analysis was performed to estimate the odds ratio and 95% confidence interval between SVR and MAFLD subtypes/hepatic condition stratified by sex. Results: Participants with MAFLD subtypes had a significant lower value of SVR compared with those without MAFLD(P＜0.001), while high quartiles of FIB-4 and NFS also showed a decreasing value of SVR in comparison with its lower quartiles (P for trend＜0.001). The lowest quartile of SVR increased the prevalence of MAFLD subtypes [adjusted OR (95%CI): 2.96 (1.48 5.93) male /3.30(1.46 7.46) female for diabetes-MAFLD, 1.91(1.26 2.88) male /4.48(1.91 10.49) female for overweight/obese-MAFLD and 4.01(1.46 10.98) male/2.53(1.19 5.37) female for lean-MAFLD groups] compared with the highest quartile of SVR (all P for trend＜0.001). Besides, the interaction effect of gender on the relationship between SVR and MAFLD subtypes was statistically significant (all P for interaction＜0.001).Restricted cubic spline indicated an inverse association between SVR and the risk of MAFLD subtypes with linearity (all P for non-linearity＞0.05). The lowest quartile of SVR also increases the risk of MAFLD fibrosis in both males and females. Conclusions: Our study concluded that a decrease in SVR (appendicular skeletal muscle mass divided by visceral fat area) is significantly associated with an increased prevalence of developing MAFLD subtypes and liver fibrosis in middle-aged and older persons of both genders.